Modelling and Performance Evaluation of a Multiport Converter for Active Balancing of Lithium- ion Battery Cells - Chelimela Shashidhar; Abba Haritha Reddy; Oggu Dhanunjay; K. Hareesh Kumar (International Journal of Electrical Power and Machine Systems, 2026)
In this paper, a flexible multiport DC-DC converter-based active cell balancing technique for Li-ion battery packs is presented. Cell balancing plays an important role in terms of safety, capacity utilization, and battery lifespan. For Li-ion cells in series configuration, the difference in voltages and states of charge (SOCs) leads to imbalance issues which might negatively affect their performance and shorten their lifespan. To solve these problems, the proposed technique utilizes a multiport DC-DC converter, which enables bidirectional power flow through every cell. Unlike passive cell balancing, this system features an SOC analyzer module, which constantly measures the SOC level of individual cells, and identifies imbalance. To make timely balancing choices with increased accuracy and less energy loss, a real-time monitoring framework is integrated to continually assess cell voltage, current, and SOC fluctuations. To ensure uniform charge distribution and reduce needless switching operations and thermal stress, the suggested control technique dynamically transfers energy from higher SOC cells to lower SOC cells. The whole system topology, SOC analysis process, and balancing techniques have been simulated using MATLAB/Simulink software. This software tool makes it possible to evaluate the system performance before hardware prototyping. Simulation results prove that voltage and SOC balance among cells have been successfully achieved under various charging conditions. When compared to traditional balancing methods, the balancing process exhibits faster convergence, increased energy economy, and higher overall battery pack dependability. The suggested simulation environment may be easily expanded to electric car and renewable energy storage applications and offers a scalable platform for verifying active balancing algorithms. In summary, the simulation environment with SOC measurement provides a flexible means of evaluating active cell balancing solutions.
Keywords: Active Cell Balancing; Battery management system (BMS); MATLAB/Simulink simulation; flexible multiport DC–DC converter; lithium-ion batteries; state-of- charge (SOC) estimation